Facilitated delivery of topical steroids after fractional ablative carbon dioxide laser benefits postthyroidectomy hypertrophic scar - Cen-Hung Lin; Yueh-Ju Tsai; Shun-Yu Chi; Mu-Han Hsieh; Ko-Chien Lin; Hui-Ping Lin; Shiun-Yuan Hsu; Hui-Hong Tsai; Ching-Hua Hsieh (Wolters Kluwer Medknow Publications, 2022)
Background: Thyroidectomy results in unsightly scarring at the anterior neck of the patient. Objectives: This prospective clinical study aimed to assess the effectiveness of laser assisted drug delivery (LADD) of topical steroid ointment for the treatment of postthyroidectomy hypertrophic scars. Methods: Five courses of a fractional ablative carbon dioxide laser combined with topical 0.05% clobetasol propionate were applied every 4 weeks to treat postthyroidectomy hypertrophic scars in ten adult female patients. The effectiveness was assessed by the patient themselves according to the Patient and Observer Scar Assessment Scale (POSAS) and by three different doctors according to photography evaluations before and 1 year after the first treatment. Results: Assessments of the scars by POSAS revealed significant improvements in terms of itchiness, color, softness, thickness, irregularity, and distorted appearance of the scars, albeit without any significant pain relief. In addition, all indicative characteristics of the scar, namely, vascularity, pigmentation, thickness, relief, pliability, surface area, and overall opinion, as assessed by the treating doctor and based on photographic evaluations by three different doctors, revealed significant improvements in the scars after treatment. Conclusion: In this study, we demonstrated that the topical delivery of steroids after fractional ablative carbon dioxide laser treatment showed an encouraging outcome in postthyroidectomy hypertrophic scarring.